Suppression of forest fuel thermal decomposition under the influence of liquid aerosol and water droplets with additives; MATEC Web of Conferences; Vol. 141 : Smart Grids 2017 - Shlegel N. E. Nikita Evgenjevich; Zhdanova A. O. Alena Olegovna; Kralinova S. S. Svetlana Sergeevna; Voytkov I. Ivan (2017, 2017)
Title screen